About etymological doublets in Еnglish (Philology, 2026)
The present article discusses the issue of etymological doublets in the English language. A criterion for the existence of doublets is defined and four groups of doublets are differentiated. A doublet couple is examined in more detail. A comparison is made between the frequencies of usage of the doublet series legal – loyal – leal, using a graph generated by the Google Books Ngram Viewer engine.
Keywords: etymological doublets; English language